2012
DOI: 10.1364/boe.4.000077
|View full text |Cite
|
Sign up to set email alerts
|

Determination of chronological aging parameters in epidermal keratinocytes by in vivo harmonic generation microscopy

Abstract: Skin aging is an important issue in geriatric and cosmetic dermatology. To quantitatively analyze changes in keratinocytes related to intrinsic aging, we exploited a 1230 nm-based in vivo harmonic generation microscopy, combining second- and third-harmonic generation modalities. 52 individuals (21 men and 31 women, age range 19–79) were examined on the sun-protected volar forearm. Through quantitative analysis by the standard algorithm provided, we found that the cellular and nuclear size of basal keratinocyte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
60
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 48 publications
(66 citation statements)
references
References 30 publications
3
60
0
Order By: Relevance
“…[27][28][29][30][31][32][33][34] Based on the principle of third-order nonlinear processes, the melanin-enhancement nature of label-free third-harmonic generation (THG) in HGM has been confirmed in the previous study. 28 We have also demonstrated that HGM achieved high diagnostic accuracy in nonmelanoma pigmented skin lesions such as BCC, SK, and melanocytic nevus.…”
Section: -3mentioning
confidence: 98%
See 1 more Smart Citation
“…[27][28][29][30][31][32][33][34] Based on the principle of third-order nonlinear processes, the melanin-enhancement nature of label-free third-harmonic generation (THG) in HGM has been confirmed in the previous study. 28 We have also demonstrated that HGM achieved high diagnostic accuracy in nonmelanoma pigmented skin lesions such as BCC, SK, and melanocytic nevus.…”
Section: -3mentioning
confidence: 98%
“…27,28,[31][32][33][34] The irregular THG-bright cells with dark nuclei and multiple cellular processes longer than the cell bodies were found mainly in the basal layer of the epidermis and inside certain tumors through THG microscopic imaging without any staining to the skin tissues. Due to the strong THG signals, enlarged cell volumes, and irregular shapes with several dendritic processes, the dendritic cells can be morphologically distinguished from the surrounding small, polygonal basal keratinocytes (Fig.…”
Section: Third-harmonic Generation Microscopic Features Of Melanocytesmentioning
confidence: 99%
“…THG-based diagnosis of basal cell carcinoma in vivo depends upon the polymorphous variations in the size and shape of transformed cells, compared to normal tissue and the presence of peripheral palisading cells (Tsai et al, 2014). An increase in the size of cells and nuclei in intact skin are characteristics of aging tissue, which can be quantified in vivo based on THG analyses (Liao et al, 2013). By providing information on cell and tissue morphology in a label-free manner, THG thus generates diagnostic 3D information with a resolution comparable to that of traditional histopathology.…”
Section: Virtual Optical Biopsymentioning
confidence: 99%
“…The white spots in (c) and Typically, LPs of the SC in broad area are related to skin barrier function. In addition to OCT methods, a-TT of the SC was indirectly verified via z-axial population of water content by confocal Raman spectroscopy [13,16] or was directly measured by multiphoton laser tomography [17,18]. For confocal Raman spectroscopy and confocal reflectance microscope [16], they both need the database of a-NOLs from frozen section [19] to verify the a-CLT of SC.…”
Section: Introductionmentioning
confidence: 99%